Pemberdayaan Masyarakat melalui Perpustakaan Rumah Pintar “Baskara Cendikia” Desa Sekar Kecamatan Donorojo Kabupaten Pacitan Jawa Timur - Agustiani, Happy; Aorta, Dian Tias; Wahyuningsih, Diah (ARZUSIN, 2022)
The Smart House Library was formed to help community get access learning resources while at the same time give sufficient the needs of community in Sekar Village, Donorojo District, Pacitan Regency. Sekar Village located at the western end of Pacitan City. Sekar Village has a problem, there is minimal community facilities to develop knowledge and skills of its community. The Smart House Library "Baskara Cendikia" is fully closest library service for the people of Sekar Village. Data collection methods used in this study were observation and interviews. Empowerment in Sekar Village is carried out through the "Baskara Cendikia" smart house, namely making the "Baskara Cendikia" smart house a center activity that able to improve quality of human resources and also as forum to channel interests, talents and hone community skills. The results of interviews and observations to several respondents obtained positive comments, where this library able to help children's learning, children's interest in learning technology is getting bigger, can provide a wider variety of teaching for children and they can get health facilities easily and practically